Análise de atividades de compreensão de leitura em livros didáticos de inglês como língua estrangeira na perspectiva da semântica argumentativa - Zamoner, Daiane (2012)
The present work aims to investigate activities of reading comprehension in textbooks of English as a foreign language from the perspective of argumentative semantics, and aims to make explicit the arguments present in the texts that comprise the corpus of this work, and verify if the reading comprehension questions deal with those argumentations, that is, if it has the aim to verify the students performance in noticing these arguments. The communicative approach is the central focus on teaching foreign languages, since it is expected from students that they will be able to communicate in that language. The amount of reading and writing exercises are considerably reduced on textbooks, that is due to the fact that the study of texts and respective reading activities presented on those books are pretext to: 1) the teaching of vocabulary as dictionary, with literal value, informational, and not argumentative; 2) the teaching of structures and its qualifications; 3) the teaching of oral skills. The linguistic theory that oriented this research is the Theory of Argumentation Within Language (ADL), in its actual form, Theory of Semantic Blocks (TBS). Under the perspective of this theory, the methodology consisted in analyze the texts presented in two units, in two textbooks of English as a Foreign Language. After the selection of books and units, it was analyzed the internal argumentation and the external argumentation of the titles and texts of each unit, to observe if the texts of the units explore the titles argumentations or not, and if there is a relation between these argumentations and the reading activities proposed. As a result, it was noticed that the argumentative chain evoked from the title of the unit not always assumed the same aspect of the block expressed by the text; the texts appeared, most of the time, disconnected from the textual production activity, the activities conducted to a fragmented reading and with the fostering to the use of language to communicative goals. Concluding, data seem to allow state that the analyses of texts, under the perspective of argumentative semantics, contribute not only to a language learning, but also allows students to perceive and think certain texts as argumentative chains of semantic blocks. The selected texts analysis from ADL/TBS showed the contribution that this theory can offer to professors and researchers that assume an argumentative language conception, noticing the text as an argumentative unit carried out of meanings.